The existence of kuda lumping performances in terms of character education based on the principles of Pancasila - Dionisius Heckie Puspoko Jati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The present study examines the traditional art of Kuda Lumping through the perspective of character values reflected in the principles of Pancasila. As a traditional Indonesian cultural practice, Kuda Lumping represents a local heritage with aesthetic appeal and deep moral significance relevant to social life. However, its existence faces increasing threats from globalisation and modern lifestyle changes, mainly due to a lack of artist regeneration. Using a qualitative approach with a descriptive-analytical method, data were collected via in-depth interviews with Kuda Lumping artists, community figures, art observers, and elementary school teachers and students, alongside direct observations and a review of relevant literature. The research aims to identify character values within Kuda Lumping that align with Pancasila, analyse factors influencing its sustainability, and explore strategies for its preservation as a medium for cultural and character education. The findings emphasise the importance of maintaining Kuda Lumping as part of the national cultural identity and a tool for fostering Pancasila values, especially among elementary students. The study also proposes strategic recommendations, including arts-based education programmes, digitalising performances, and enhancing support from government and cultural communities. It is hoped that Kuda Lumping will continue to flourish as both a cultural heritage and a means of character development aligned with Pancasila.